2006
DOI: 10.1021/ja065249g
|View full text |Cite
|
Sign up to set email alerts
|

Carbene vs Olefin Products of C−H Activation on Ruthenium via Competing α- and β-H Elimination

Abstract: Bulky pincer complexes of ruthenium are capable of C-H activation and H-elimination from the pincer ligand backbone to produce mixtures of olefin and carbene products. To characterize the products and determine the mechanisms of the C-H cleavage, reactions of [RuCl(2)(p-cymene)](2) with N,N'-bis(di-tert-butylphosphino)-1,3-diaminopropane (L1) and 1,3-bis(di-tert-butylphosphinomethyl)cyclohexane (L2) were studied using a combination of X-ray crystallography, NMR spectroscopy, and DFT computational techniques. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 57 publications
(34 reference statements)
1
52
0
3
Order By: Relevance
“…The X-ray structure of this 18-e species reveals a trans-Cl-Ru-H center supported by a dehydrogenated 3b unit, which now acts as a three-coordinate mer ligand through the two P atoms and the η 2 -olefin moiety. A similar structure has already been reported by Gusev et al [27] The coordination sphere in 7 is completed by a P(OMe)Ph2 group, likely from the P-N bond methanolysis [28] of a second 3b molecule. The hydridic resonance in 7 is found at -13.58 ppm (apparent td), and the olefinic signals appear at δ 5.38 (dd, 3 JHP = 13.6, The isolated 3b/Ru(II) complexes 4 and 7 were tested in the model benzylation reaction of aniline.…”
Section: Complex Chemistrysupporting
confidence: 72%
“…The X-ray structure of this 18-e species reveals a trans-Cl-Ru-H center supported by a dehydrogenated 3b unit, which now acts as a three-coordinate mer ligand through the two P atoms and the η 2 -olefin moiety. A similar structure has already been reported by Gusev et al [27] The coordination sphere in 7 is completed by a P(OMe)Ph2 group, likely from the P-N bond methanolysis [28] of a second 3b molecule. The hydridic resonance in 7 is found at -13.58 ppm (apparent td), and the olefinic signals appear at δ 5.38 (dd, 3 JHP = 13.6, The isolated 3b/Ru(II) complexes 4 and 7 were tested in the model benzylation reaction of aniline.…”
Section: Complex Chemistrysupporting
confidence: 72%
“…[5] However, according to density functional theory (DFT) calculations, the PCP pincer complex [RuCl{HC(CH 2 NHPtBu 2 ) 2 }] (A) was postulated to be an unstable intermediate with square-planar coordination geometry and a triplet ground state (IS). [6] Therefore, the related PNP pincer complexes [RuX{N(SiMe 2 CH 2 PtBu 2 ) 2 }] (X = F (B F ), Cl (B Cl ), OTf (B OTf )) remain the only square-planar ruthenium(II) compounds that are experimentally accessible and have an IS ground-state configuration. [7] DFT calculations showed that the highest singly occupied molecular orbital (SOMO) of B Cl exhibits strong d xz -orbital character owing to the p interaction with the disilylamido p donor (Scheme 1, middle).…”
mentioning
confidence: 99%
“…However, this interaction is not sufficient to effect spin pairing. Accordingly, square-planar d 6 14-electron complexes with an electronic low-spin configuration are not known, to date. [8,9] Starting from the chelating amino ligand HN(CH 2 CH 2 PiPr 2 ) 2 (HPNP iPr ), we recently reported the synthesis of octahedral ruthenium(II) amino complexes and the corresponding five-coordinate amides.…”
mentioning
confidence: 99%
“…Geburtstag gewidmet Die Koordinationschemie von d 6 -Ionen der Gruppe 8 wird dominiert von oktaedrischen Komplexen. Vierfachkoordination tritt vor allem bei tetraedrischen Eisenkomplexen auf, die im High-Spin-Zustand (S = 2, HS) vorliegen.…”
unclassified